Echoes of History: Life Stories of Priests, Nuns and Brothers in South Australia - Palombi, Antonetta (Curtin University, 2024)
Using methods drawn from oral history and life writing, this study is a creative non-fiction work focused on the life stories of Catholic priests and nuns in South Australia aged over 60 years. This generation of priests and nuns have experienced unprecedented social, political and religious change during their lives and period of ordination, all of which is reflected in their life stories.